The Other 99%: The Conservation and Biodiversity of Invertebrates 1999
DOI: 10.7882/rzsnsw.1999.011
|View full text |Cite
|
Sign up to set email alerts
|

Acarine (mite) communities colonizing rehabilitated bauxite mine pits in the jarrah forest of Western Australia

Abstract: This study investigated the abundance and diversity of acarine (mite) communities in the soil of rehabilitated bauxite mine pits of the Northern Jarrah Eucalyptus marginata forest in southwest Australia. The areas selected had been subject to various revegetation techniques and ranged in age from 2 to 20 years. The study found that more than ten years is required for rehabilitated areas to generate mite abundance and diversity comparable to adjacent unmined forest. The use of mites as indicators of ecosystem r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Mites Another soil and litter layer group, which includes both detritus‐feeding and predatory forms, is the Acarina or mites. The cryptostigmatid species are the predominant detritus feeders (Table 4) (Cuccovia & Kinnear 1999). This group was numerically dominant in most of Alcoa’s restored plots and cryptostigmatid density was significantly correlated with post‐mining age (Table 4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mites Another soil and litter layer group, which includes both detritus‐feeding and predatory forms, is the Acarina or mites. The cryptostigmatid species are the predominant detritus feeders (Table 4) (Cuccovia & Kinnear 1999). This group was numerically dominant in most of Alcoa’s restored plots and cryptostigmatid density was significantly correlated with post‐mining age (Table 4).…”
Section: Introductionmentioning
confidence: 99%
“…However, richness in the oldest pit was still well below that of the forest control. Increased density in this group appears also to be associated with increases in the canopy and litter cover (Cuccovia & Kinnear 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference reflects their preferred habitat of litter and soil rather than logs, but could also relate to their small size which allows them to pass through the mesh and hence yielded lower capture rates in this study. In a previous study in rehabilitated bauxite mines in the jarrah forest, Cuccovia and Kinnear (1999) found a steady increase in litter mite abundance and species richness from two-year-old through to 20-year-old sites. Unmined forest sites also had higher abundance and richness.…”
Section: Discussionmentioning
confidence: 81%
“…For example, high numbers of oribatid mites (including mites in the Family Phthiracaridae), which are important and characteristic soil and litter decomposers (Coleman et al 2004), were recovered from fine wood samples in both plots. In a similar study of the mite fauna in restored jarrah forest, these oribatid mites were not found until 20 years after initial restoration, notably in sites with dense litter build up (Cuccovia & Kinnear 1999). Other groups found only in wood treatment plots (Diplopoda, Dermaptera and Blattidae) are generally associated with decomposing wood and litter, on which they feed, while Opiliones and Myrmeleontidae larvae are predaceous upon invertebrates that dwell in litter and wood.…”
Section: Discussionmentioning
confidence: 89%